METODE HOLT DOUBLE EXPONENTIAL SMOOTHING UNTUK PERAMALAN PRODUKSI DAGING AYAM KAMPUNG - Ari Intahaya; Nur Salamah; Hidayatul Ummah; Faradillah Siska Alfiani; Zahrotul Wardah Fadhlia; Ahmad Isroil (Universitas Negeri Surabaya, 2025)
This study aims to forecast the production of free-range chicken in East Java using the Holt-Double Exponential Smoothing method. By utilizing production data from the past several years, this method was chosen for its ability to capture existing trend patterns. The analysis results indicate that the method provides a high level of accuracy in forecasting. In general, the production of free-range chicken is expected to increase in most regions, although some areas may experience a decline. It is expected that farmers and local governments would use the study's conclusions as a foundation for their decision-making in order to preserve the stability and sustainability of free-range chicken production.